Inter-industry labour mobility in Britain since 1959 - Sleeper, R (1972)
﻿ The present study is an analysis of inter-industry labour flows between 1959 and 1968. The data were provided by the Department of Employment (DE) and are derived from an annual one per cent sample survey of employees holding national insurance cards. Their reliability is subject to several limitations but on the whole they provide good approximations of the actual figures. The study begins with an introductory chapter in which the findings of macro analyses of labour supply and micro investigations into local labour markets are examined in order to demonstrate the need for the inter-industry approach taken here. The manpower flow data are introduced at the end of this chapter where their limitations are discussed. The main body of the thesis is contained in the next six chapters. These can be divided into two parts. Chapters II-IV analyze the role of non-cyclical forces in determining manpower flows between industries. Chapter II examines net flows between manufacturing and non-manufacturing. It analyzes the contribution these net flows make to overall changes in industrial employment levels and demonstrates that manufacturing relies heavily on net recruitment from certain non-manufacturing industries which, in turn, experience large net intakes of persons outside employment. The chapter also shows that there is a tendency for young persons to enter and leave the labour force through the service sector and to spend the prime of their working lives in manufacturing where wages are higher. Chapter III analyzes gross manpower movements in and out of industries. The first half examines each industry's total inflows and outflows as a proportion of its employment level. This provides a measure of the industry's labour turnover rate. Industries with high turnover rates were found with two exceptions either to have high rates of employment growth or to pay low average wages. The second half examines the relative sizes of labour flows between industries and demonstrates that manpower movements between certain pairs of industries are much greater than would occur if flows were randomly determined. In other words, the industry a mobile worker enters is to some extent a function of his previous industry of employment. Chapter IV analyzes the causes of these neighbourhood relationships between industries. The first half constructs a measure of locational and occupational similarities between industries. The resulting formula provides estimates of the degree of neighbourliness between industries that are remarkably close to those derived from the inter-industry mobility data. The chapter also considers the importance of relative wages in determining neighbourhood relationships and reports that these play a subordinate role. Chapter V begins the discussion of the trade cycle's impact The first half examines net movements of manpower between manufacturing and non-manufacturing and finds that they are positive in upswings and negative in downswings. Moreover, net flows increase as a proportion of total manufacturing employment changes in the late stages of each upswing,, This reflects the favourable manufacturing wage differential and the intensification of competition for manpower already in employment as the number of persons without jobs and seeking work dwindles. Net manufacturing inflows were, however, found to decline in absolute terms in the late stages of each upswing. The second half of the chapter examines gross manpower flows between manufacturing and non-manufacturing. It shows that the decline in net male flows during the late stages of each upswing is due both to a fall in gross inflows and a rise in outflows. The lower inflow is due to a decline in the number of persons in non-manufacturing suitable for recruitment into manufacturing while the higher outflow reflects increasing competition from the non-manufacturing sector. Net female flows fall by much less in the late stages of an upswing. Gross inflows continue to increase but outflows rise faster. This is because the female labour supply is more elastic and movements of women between manufacturing and non-manufacturing respond more readily to relative demand changes. Chapter 6 analyzes in greater depth the effects of a tightening labour market on the inter-industry mobility process It shows that the manufacturing sector suffers most from manpower shortages at the peak of the cycle even though its plants pay the highest wages. This is attributable to greater cyclical fluctuations in manufacturing labour demand, greater skill requirements, and increasing competition from non-manufacturingo The relative importance of each of the last two factors can be expected to vary between individual manufacturing industries Engineering and metals plants should experience greater recruitment difficulties owing to skill differences, while plants in industries that are close neighbours to non-manufacturing industries could be expected to suffer from increasing competition from the non-manufacturing sector. These theories are tested econometrically on manpower flow data for movements between non-manufacturing and individual manufacturing industries and are supported by the results. Chapter 7 analyzes manpower flows between the engineering and metals industries. These are shown to be affected strongly by changes in the composition of final product demand. Post war cycles in Britain have been led by the swings in consumer expenditure on durable goods and lagged by fluctuations in plant and machinery investment. Plants producing both types of goods are found in engineering and metals industries. In some cases both types of goods may be produced in the same factoryo Consequently there is considerable competition for scarce manpower between these two sectors of final demand. The effect of the lag in the timing of demand recovery between them is, however, to provide consumer durables producers with a competitive advantage. Since their manpower requirements start to expand at a time when the labour market is relatively slack, they have the opportunity to pre-empt the labour supply. Capital goods producers must then wait until the start of the downswing before they can recruit all the manpower they require This suggests that capital goods producers face the most serious manpower shortages at the peak of the boom and an investigation of cyclical fluctuations in the time customers have to wait for deliveries of plant and machinery provides qualified support for this view. Chapter 8, the conclusion,contains a summary of the findings of the study and a discussion of its implications for future research and policy making. It considers various methods of achieving a change in the industrial distribution of employment and argues that the introduction of relative wage changes to achieve this objective is best regarded as a policy of last resort implemented only after its likely impact on flow patterns and comparability claims have been carefully analyzed. The advantages of discriminatory taxes on labour - such as the Selective Employment Tax - over relative wage changes is that they do not induce comparability claims from workers who lose their position in the earnings structure. More research into interindustry mobility patterns is recommended to provide a basis for future manpower planning and the possible introduction of new types of discriminatory employment taxes to assist in the implementation of such plans.